ELDERLY SPATIAL IDEALS AND COMFORT IN DOMESTIC SPACE USE: A STUDY OF BUGIS VERNACULAR HOUSING - Putri Nur Sakinah; Arina Hayati; Muhammad Faqih (Center for Scientific Publication, 2026)
With increasing age, elderly individuals experience declines in physical and cognitive functions, requiring adaptations in their daily activities and living environments. In rural contexts, elderly residents often maintain strong adherence to cultural values and traditional housing practices, adjusting their activities and bodily abilities rather than modifying the spatial configuration of their homes. One group that continues to inhabit vernacular houses is the Bugis community in Tolitoli, Central Sulawesi, Indonesia. This study aims to examine the relationship between the health conditions of rural elderly and their spatial ideals and comfort in using domestic spaces within Bugis vernacular houses. The research employed a mixed-method approach, combining qualitative methods (participant observation and in-depth interviews) and quantitative methods (questionnaire survey analyzed through cross-tabulation and Fisher's Exact Test). The qualitative findings reveal that elderly residents hold strong spatial ideals rooted in cultural familiarity, which inform how they adapt to domestic spaces amid declining health conditions. Rather than modifying spatial configurations, elderly residents adjust their daily activities in alignment with their existing spatial ideals and accumulated spatial knowledge. Three aspects of spatial quality were identified as relevant to this adaptive process: personal safety, sensory comfort, and functionalities of space. Personal safety is especially significant for elderly with cognitive impairments, while sensory comfort, particularly tactile perception, plays a key role for those with visual impairments. Functionalities of space support elderly independence by enabling mobility and daily activity management within the domestic environment. The quantitative findings further indicate that health conditions relate significantly to two spatial comfort aspects: room size and floor surface texture, both corresponding to personal safety and sensory comfort needs. Overall, the findings suggest that the health conditions of rural elderly relate to their spatial ideals and comfort in nuanced ways, shaped by longterm cultural familiarity with the vernacular dwelling environment.